근거기반 지역사회 심뇌혈관질환 예방관리 목표설정과 모니터링 경험 - 이혜진(HeyJean Lee); 문지영(Jiyoung Moon); 최단비(Danbi Choi); 백연희(Yeonheui Baeg); 박영권(Young-Kwon Park); 조은희(Eun-Hee Cho); 허애영(Ae-Young Her); 김용훈(Yong Hoon Kim); 김정민(Jung Min Kim) (보건교육건강증진학회지, 2019)
Objectives: This study aimed to share experience of goal setting and monitoring in local government based on Health Plan 2020. Methods: We calculated 16 indices among 27 of Health Plan 2020. We applied ‘Better to the Mean’ of peer community for indices were under mean of similar four provinces. We applied ‘Better to the Mean’ of national mean for indices were beyond the mean of peer communities. We applied the ‘Better to the Best’ for indices were above the national mean. Results: We applied ‘Better to the Mean’ of peer communities for intake of sodium, awareness of own blood pressure, rate of treated hypertension, awareness of own blood glucose, rate of treated diabetes, awareness of hypercholesterolemia, rate of treated hypercholesterolemia, rate of controlled hypercholesterolemia, prevalence of stroke, awareness of symptoms of stroke. We applied ‘Better to the Mean’ of nation to rate of sufficient walking, annual screening rate of fundus, and rate of controlled diabetes. We applied ‘Better to the Best’ for prevalence of hypertension, rate of controlled hypertension, and annual screening rate of microalbuminuria. Conclusions: G province set the goal based on evidence and conducted monitoring. We expected this study to be useful reference. KCI Citation Count: 0